Inhaled hypertonic saline in preschool children with cystic fibrosis (SHIP): a multicentre, randomised, double-blind, placebo-controlled trial. Issue 9 (September 2019) - Ratjen, Felix; Davis, Stephanie D; Stanojevic, Sanja; Kronmal, Richard A; Hinckley Stukovsky, Karen D; Jorgensen, Neal; Rosenfeld, Margaret; ,; Kerby, Gwen; Kopecky, Carol; Anthony, Meg; Mogayzel, Peter; et al.
Summary: Background: Inhaled hypertonic saline enhances mucociliary clearance, improves lung function, and reduces pulmonary exacerbations in people with cystic fibrosis older than age 6 years. We aimed to assess the effect of inhaled hypertonic saline on the lung clearance index (LCI2·5 )—a measure of ventilation inhomogeneity—in children aged 3–6 years with cystic fibrosis. Methods: The Saline Hypertonic in Preschoolers (SHIP) Study was a randomised, double-blind, placebo-controlled trial at 25 cystic fibrosis centres in Canada and the USA. Eligible participants were aged 36–72 months; had a confirmed diagnosis of cystic fibrosis; were able to comply with medication use, study visits, and study procedures; and were able to complete at least two technically acceptable trials of multiple breath washout (MBW). Participants were randomly assigned (1:1) via a web-based data entry system that confirmed enrolment eligibility to inhaled 7% hypertonic saline or 0·9% isotonic saline nebulised twice daily (for no more than 15 min per dose) for 48 weeks. Permuted block randomisation was done separately for participants aged 36–54 months and those aged 55–72 months to ensure approximate balance by treatment group in the two age groups. The primary endpoint was the change in the LCI2·5 measured by nitrogen MBW from baseline to week 48. All study sites were trained and certified in MBW. Analysis was by intention to treat. This study is registered with Clinicaltrials.gov, number NCT02378467 . Findings: Between April 21, 2015, and Aug 4, 2017, 150 participants were enrolled and randomly assigned, 76 to the hypertonic saline group and 74 to the isotonic saline group. Overall 89% of the MBW tests produced acceptable data. At 48 weeks, treatment with hypertonic saline was associated with a significant decrease (ie, improvement) in LCI2·5 compared with isotonic saline (mean treatment effect −0·63 LCI2·5 units [95% CI −1·10 to −0·15]; p=0·010). Six participants in the hypertonic saline group had ten serious adverse events and eight participants in the isotonic saline group had nine serious adverse events. The serious adverse events reported were cough (two patients [3%] in the hypertonic saline group vs three [4%] in the isotonic saline group), gastrostomy tube placement or rupture (two [3%] vs one [1%]), upper gastrointestinal disorders (one [1%] vs two [3%]), distal intestinal obstruction syndrome (one [1%] vs one [1%]), and decreased pulmonary function (none vs one [1%]). None of these serious adverse events was judged to be treatment related. Interpretation: Inhaled hypertonic saline improved the LCI2·5 in children aged 3–6 years, and could be a suitable early intervention in cystic fibrosis. Funding: Cystic Fibrosis Foundation.